2019
DOI: 10.22456/1679-9216.96578
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Dogs to Different Housing Systems

Abstract: Background:The hypothalamic-pituitary-adrenal (HPA) axis undergoes adaptations throughout housing system that might contribute to the avoidance of adverse effects of welfare status in dogs housed in a shelter. Nevertheless, the influence of housing systems and stabling time on glucose and PCV changes is little known. The purpose of the present study was to evaluate the patterns of cortisol, glucose and PCV in dogs housed in a kennel and normal environments, evaluating the differences between housing systems, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In previous studies, it has been reported that if the pain is effectively controlled, the clinical signs associated with this sign are minimal or null during the immediate post-operative period. For example, Fazio et al (2015) observed that both the behavioral and hematological changes associated with pain did not occur during the immediate post-operative period, which is indicative for these authors of antinociceptive efficacy during surgery, similar to that observed in some studies (Morgaz et al 2013;Berry 2015). For this reason, if no changes are observed during the immediate post-operative period, the analgesic requirements are reduced in this period, in addition to the fact that if the scores obtained by structured scales to assess behavior remain low, the frequency of subsequent evaluation can be extended in the interval.…”
Section: Post-surgical Pain Evaluation Scalesmentioning
confidence: 99%
“…In previous studies, it has been reported that if the pain is effectively controlled, the clinical signs associated with this sign are minimal or null during the immediate post-operative period. For example, Fazio et al (2015) observed that both the behavioral and hematological changes associated with pain did not occur during the immediate post-operative period, which is indicative for these authors of antinociceptive efficacy during surgery, similar to that observed in some studies (Morgaz et al 2013;Berry 2015). For this reason, if no changes are observed during the immediate post-operative period, the analgesic requirements are reduced in this period, in addition to the fact that if the scores obtained by structured scales to assess behavior remain low, the frequency of subsequent evaluation can be extended in the interval.…”
Section: Post-surgical Pain Evaluation Scalesmentioning
confidence: 99%